Commentary: the importance of education and vaccination in reducing the risk of hepatitis infection among nursing students - Jayne Cutter (International Nursing Review, 2011)
Background: Occupational acquisition of blood-borne viral infection has been reported following contact with blood and body fluids. Nursing students may be at particular risk because of their inexperience. Standard precautions, vaccination against hepatitis B vaccination and appropriate post-exposure prophylaxis will reduce the risk of infection in the event of an advers exposure to blood and body fluids.Aim: Yamazhan et al. who explored nursing students’ knowledge on hepatitis together with their immunization status. This commentary discusses the findings of this study Evaluation: Universities in Turkey encourage the uptake of hepatitis B vaccination students, suggesting a high commitment to reducing the risk of this infection. However, knowledge of hepatitis, its mode of transmission and risk of infection following adverseexposure to blood and body fluids is variable between universities and needs to be enhanced to improve practice and fully protect nursing students from infection Implications: All universities in Turkey should deliver a standardized education package to ensure that nursing students have a sound knowledge of all blood-borne infections. Vaccination programmes must continue to ensure consistent protection aginst hepatitis B.